Visual Inhibition Measures Predict Speech-in-Noise Perception Only in People With Low Levels of Education - Knight, Sarah; Heinrich, Antje (Frontiers in Psychology, 2019)
Inhibition – the ability to suppress goal-irrelevant information – is thought to be an important cognitive skill in many situations, including speech-in-noise (SiN) listening. Both inhibition and SiN perception are thought to worsen with age, but attempts to connect age-related declines in these two abilities have produced mixed results even though a clear positive relationship has generally been hypothesised. We suggest that these inconsistencies may occur because listener-based demographic variables such as educational attainment modulate the relationship between inhibition and SiN perception. We tested this hypothesis with a group of 50 older adults (61-86 years, mean: 69.5) with mild-to-moderate age-related hearing loss (8-53 average dB HL, mean: 25.3 dB HL). Participants performed a visual Stroop task and two SiN tasks. In a Stroop task one stimulus dimension is named while a second, more prepotent dimension is ignored. Results show a clear influence of educational attainment relationship of visual Stroop scores to SiN performance, but only for those with lower levels of education. These findings highlight for the first time the importance of considering potentially heterogeneous demographic listener variables when analysing cognitive tasks and their relationship to SiN perception.